ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI BUDIDAYA KERAMBA IKAN DI KECAMATAN SIAK HULU KABUPATEN KAMPAR - Suerni, Suerni; Rita, Iyan Yani; Rahmita, Ningsih B. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
The purpose of this study was to determine the factors that influence the production of fish cage cultivation in Siak Hulu District, Kampar Regency. The population is all cage owners in Siak Hulu Subdistrict of Kampar Regency as many as 220 people, with a total sample of 69 people. The sampling technique uses random sampling. The type of data used is primary data and secondary data, while the data collection technique uses a questionnaire. Data analysis method used in this study is to use multiple linear regression. The results showed that the production of fish cage cultivation in Siak Hulu District, Kampar Regency was influenced by land and natural resources, labor and capital factors. This means that as land and natural resources, labor and capital factors increase, fish cage production also increases.Keywords: Production, Land and Natural Resources, Labor, Capital